Biodegradable Mineralized Collagen Plug for the Reconstruction of Craniotomy Burr-Holes: A Report of Three Cases. Issue 1 (September 2015) - Qiu, Zhiye; Zhang, Yuqi; Zhang, Ziqiang; Song, Tianxi; Cui, Fuzhai
Objectives: In this case report, we describe the design, fabrication and clinical outcomes of a novel bioresorbable, mineralized collagen burr-hole plug for the reconstruction of craniotomy burr-holes. Methods: Mineralized collagen burr-hole plugs were fabricated via a biomimetic mineralization process. The biomimetic mineralized collagen has a similar chemical composition and microstructure to natural bone tissue, thereby possessing good biocompatibility and osteoconductivity. The mineralized collagen burr-hole plugs were implanted into three patients, and clinical outcomes were evaluated at one-year follow-ups. Results: All bone defects healed very well using the mineralized collagen burr-hole plugs, and there were no adverse reactions at the surgical sites. Conclusions: The clinical outcomes indicated that the mineralized collagen was effective for reconstructing burr-holes in the skull after craniotomy.